2022
DOI: 10.56578/jimd010206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Artificial Intelligence in Enhancing the Human Resource Practices

Abstract: Artificial intelligence, in a larger sense, refers to computers that have human intelligence-specific capabilities such as obtaining information, perceiving, seeing, thinking, and making decisions. At first glance, artificial intelligence, often known as "Artificial Intelligence" (AI) in the literature, causes everyone to associate something distinct. According to researches, the concept of artificial intelligence evokes an electro-mechanical robot replacing human beings, but everyone involved in this field is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[68,69] Some other works are in refs. [70][71][72][73][74]. However, if the resulting solution does not satisfy any of the following conditions, then that solution will not be advantageous in discussing celestial systems.…”
Section: Acceptability Criteria For Physically Realistic Modelsmentioning
confidence: 99%
“…[68,69] Some other works are in refs. [70][71][72][73][74]. However, if the resulting solution does not satisfy any of the following conditions, then that solution will not be advantageous in discussing celestial systems.…”
Section: Acceptability Criteria For Physically Realistic Modelsmentioning
confidence: 99%
“…Throughout the existing studies, it can be found that current researchers are increasingly focusing on the motivation and promotion of team member’s creative behaviors in various industries [ 21 , 22 , 23 ]. However, most studies on individual creative behaviors in the Chinese context are conducted on students, team leaders, or non-cultural creative industry practitioners, and few studies focus on team members or even cultural innovation team members as a group [ 24 , 25 , 26 ]. Motivating team members at the mental level is one of the important means for team managers to promote their members’ creative behaviors, but the effectiveness of this needs to be confirmed by further research.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of smart factories, the improvement of product quality and productivity rates are recognized as the main benefits of the 4th industrial revolution, while the improvement of the quality of services is noticeable in health ( Jovanovic et al, 2022b ). The general progress in the field of IT, such as affordable computing resources and emergence of appropriate algorithms, has led to rapid development of technologies, especially AI and ML, which in turn evolved into base tools for solving difficult problems in various fields, including finance, industry, healthcare, human resources, software development and defect prediction, agriculture and logistics, just to name few ( Buchanan, 2019 ; Peres et al, 2020 ; Yu, Beam & Kohane, 2018 ; Dobrojevic & Bacanin, 2022 ; AVSystem, 2020 ; Biliavska, Castanho & Vulevic, 2022 ; Zheng et al, 2022 ; Holliday, Sani & Willett, 2015 ; Muhammad, Abdullah & Samsiah Sani, 2021 ; Mohamed Nafuri et al, 2022 ; Abdul Rahman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%